Biointerfaces: Light‐Responsive Hierarchically Structured Liquid Crystal Polymer Networks for Harnessing Cell Adhesion and Migration (Adv. Mater. 27/2017). Issue 27 (July 2017) - Koçer, Gülistan; ter Schiphorst, Jeroen; Hendrikx, Matthew; Kassa, Hailu G.; Leclère, Philippe; Schenning, Albertus P. H. J.; Jonkheijm, Pascal
Abstract : Light‐responsive liquid‐crystal polymer networks are presented by Albertus P. H. J. Schenning, Pascal Jonkheijm, and co‐workers in article number1606407 as new hierarchically structured biointerfaces. Micrometer‐scale topographical cues with simultaneous changes in nanoscale roughness lead to materials that harness cell adhesion and migration. In situ, dynamic control of cell behavior on biomaterials and interfaces improves their performance to be analogous to natural cellular microenvironments.